An elastic polyester-fish scale scaffold for sequential-release of biofactors to facilitate bone regeneration in postmenopausal osteoporosis with diabetes - Junwu Wang; Lanhong Guo; Wenjie Zhao; Shuai Chen; Yilong Huang; Tian Luan; Hao Chen; Peng Ma; Wen Min; Jinghuan Huang; Jingfeng Li (Chemical Engineering Journal, 2026)

Multifunctional aramid honeycombs filled with PVDF composite foams via in situ supercritical foaming: Nearly-isotropic broadband microwave absorption and mechanical reinforcement - Yang Ou; Hongbo Hou; Jingfeng He; Wenhan Cui; Jiaju Zhu; Li Ma; Fanbin Meng (Chemical Engineering Journal, 2026)

Strengthening carbon sinks in Tibetan Plateau alpine grasslands over the past four decades - Yuyang Wang; Yaoming Ma; Jingfeng Xiao; Weiqiang Ma; Zhipeng Xie; Zhiyong Ding; Kesi Liu (Agricultural and Forest Meteorology, 2026)

A coupled rockfall-bridge damage assessment method integrating trajectory simulation and intrusion detection - Jingfeng Zhang; Jie Ma; Jizhuang Guo; Jiaxin Luo; Han Bao; Huaimao Yang (Engineering Structures, 2026)

Forecasting of large-scale tea anthracnose in mountainous region of China though integration of multi-source habitat information with spatiotemporal phenological corrections - Yujuan Huang; Huiqin Ma; Cong Xu; Lin Yuan; Jingfeng Huang; Zijing Jin; Jingcheng Zhang (European Journal of Agronomy, 2026)

Temporal Memory Mechanisms and Biome‐Specific Drivers of Ecosystem Carbon Flux: Insights From Explainable Deep Learning Modeling - Teng Ma; Wei He; Shuangxi Fang; Jingfeng Xiao; Ngoc Tu Nguyen; Hua Yang; Peipei Xu; Chengcheng Huang; Mengyao Zhao; Shuai Liu; Xinhui Lei; Ziyi Huang (Global Change Biology, 2026)
Ecosystem carbon dynamics are governed by complex temporal dependencies and environmental interactions, yet these processes remain poorly understood and quantified across diverse biomes. Here, we developed an explainable LSTM‐Attention framework that integrates LSTM networks, attention mechanisms, and gradient‐based attribution methods to reveal temporal dependencies in ecosystem carbon flux responses by analyzing eddy covariance flux measurements from 71 sites spanning eight North American biomes. Using this approach, we identified three distinct temporal memory patterns governing carbon flux responses. Grasslands exhibit short‐term memory dominance with exponentially increasing temporal contributions from distant to recent past. Deciduous broadleaf forests and wetlands show long‐term memory dominance, with deciduous broadleaf forests displaying the strongest historical dependence (attribution values declining from 0.30 at 6 months to 0.045 at 1 month). Croplands and evergreen needleleaf forests demonstrate U‐shaped dual memory patterns. Building on these temporal patterns, we identified biome‐specific environmental drivers operating within each memory framework: wetlands primarily controlled by soil moisture, evergreen needleleaf forests by radiation, and closed shrublands by vapor pressure deficit. Beyond individual drivers, we uncovered critical nonlinear interactions that diverged from linear correlations at most sites (55 of 71 with ρ

Removal and toxic intervention of polystyrene microplastics and nanoplastics by magnetic nano-Fe3O4 in spermatogonial GC-1 cells - Cheng Cheng; Yanfan Cui; Yujie Wang; Jingfeng Huang; Jiale Ma; Tao Luo; Wen Chen (Reproductive Toxicology, 2025)

Mechanical Behavior and Fracture Evolution of Non-Persistent Rock Joints Using Digital Image Correlation - Xinggang Wang; Xin Jin; Shuaishuai Wang; Jingfeng Shi; Yong Xu; Shuqi Ma; Qilin Yan (Geotechnical and Geological Engineering, 2025)

Machine learning enhanced bridge vulnerability quantification under rockfall hazards - Jingfeng Zhang; Yifan Jing; Jie Ma; Jiaxin Luo; Han Bao; Shizhi Chen (Engineering Geology, 2025)

An overview on the legacy and risks of Polychlorinated Biphenyls (PCBs) and Organochlorinated Pesticides (OCPs) in the polar regions - Peng Zhang; Jing Wang; Andrew Sweetman; Linke Ge; Rongguang Xing; Hao Ji; Jingfeng Yan; Qian Xiao; Yaqing Cui; Hongrui Ma; Sisi Xu (Marine Pollution Bulletin, 2024)

Hormesis and synergistic effects of disinfectants chloroxylenol and benzethonium chloride on highly efficient heterotrophic nitrification-aerobic denitrification functional strain: From performance to mechanism - Yi Guo; Jingfeng Gao; Yingchao Cui; Yifan Zhao; Biao Ma; Liqin Zeng; Hao Chen (Journal of Hazardous Materials, 2024)

Environmental benefits and supply dynamics of electric vehicles sharing: From a systematic perspective of transportation structure and trip purposes - Shunchao Wang; Jingfeng Ma; Qi Cao; Lichao Wang (Transportation Research Part D: Transport and Environment, 2024)

Significantly enhanced biodegradation of profenofos by Cupriavidus nantongensis X1T mediated by walnut shell biochar - Genrong Zhang; Jingfeng Xue; Yufei Zhang; Jia Ye; Nan Zhang; Liancheng Fang; Taozhong Shi; Xin Ma; Hui Li; Rimao Hua (Journal of Hazardous Materials, 2024)

Aflatoxin B1-induced early developmental hepatotoxicity in larvae zebrafish - Chi Feng; Hongxia Bai; Xu Chang; Zhixuan Wu; Wu Dong; Qianqian Ma; Jingfeng Yang (Chemosphere, 2023)

Identifying the heterogeneous effects of road characteristics on Motorcycle-Involved crash severities - Shunchao Wang; Jingcai Yu; Jingfeng Ma (Travel Behaviour and Society, 2023)

Solar-induced chlorophyll fluorescence captures photosynthetic phenology better than traditional vegetation indices - Jingru Zhang; Alemu Gonsamo; Xiaojuan Tong; Jingfeng Xiao; Cheryl A. Rogers; Shuhong Qin; Peirong Liu; Peiyang Yu; Pu Ma (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Anti-rolling analysis and resistance optimization of a new anti-rolling hydrofoil for the trimaran vessel - Yihan Zhang; Jingfeng Hu; Shan Ma; Ping Wang (Ocean Engineering, 2023)

Proteomic differences between Vibrio tubiashii strains with high- or low-virulence levels isolated from diseased ivory snail Babylonia areolata - Ruixuan Wang; Xiaojing Liu; Jiangyong Wang; Huizhu; Xiaozhi Lin; Jingfeng Sun; Hongli Mou; Ting Zhang; Xilan Ma (Aquaculture International, 2022)

Spatial distribution characteristics of bacterial community structure and gene abundance in sediments of the Bohai Sea - Quanrui Chen; Jingfeng Fan; Jie Su; Hongxia Ming; Zhihao Sun; Mengfei Li; Xiaohui Zhao; Yantao Wang; Yingxue Zhang; Huizhen Zhang; Yuan Jin; Xiaowan Ma; et al. (Acta Oceanologica Sinica, 2020)

Spatial econometric analysis of carbon emission intensity in Chinese provinces from the perspective of innovation-driven - Song Liang; Jingfeng Zhao; Shumin He; Qingqing Xu; Xin Ma (Environmental Science and Pollution Research, 2019)

Etiology and epidemiology of viral diarrhea in children under the age of five hospitalized in Tianjin, China - Yabo Ouyang; Hui Ma; Min Jin; Xinwei Wang; Jingfeng Wang; Lu Xu; Shuxiang Lin; Zhiqiang Shen; Zhaoli Chen; Zhigang Qiu; Zhixian Gao; Lin Peng; et al. (Archives of Virology, 2012)

Genetic linkage maps of barfin flounder (Verasper moseri) and spotted halibut (Verasper variegatus) based on AFLP and microsatellite markers - Hongyu Ma; Songlin Chen; Jingfeng Yang; Siqing Chen; Hanwen Liu (Molecular Biology Reports, 2011)

Isolation of sex-specific AFLP markers in Spotted Halibut (Verasper variegatus) - Hongyu Ma; Songlin Chen; Jingfeng Yang; Xiangshan Ji; Siqing Chen; Yongsheng Tian; Jinzhen Bi (Environmental Biology of Fishes, 2010)